Kinetics of manganese(III) Oxidation of Anisic Acids and Alcohols - Balasubhrmanian, V.; Muthukumaran, S.; Loganayagi, A.; Karthikeyan, N. (Asian Journal of Chemistry, 2010)
Manganese(III) oxidation of anisic acids and glycols has been studied in the presence of perchioric acid. The reaction exhibits a total second order kinetics, first order in each reactant. The effect of temperature on the oxidation has been investigated in the temperature range 293-323 K and the thermodynamic parameters have been calculated. The formation of the product in each case is accounted by a suitable mechanism.